Prioritizing Play, Universal Design for Learning, and Nature-Based Learning: Professional Development for Educators - Melissa Rodriguez-Meehan; Marisa Kofke; Kyra Stephenson (Educational Considerations, 2026)
This article provides insight into the process and implementation of a professional development workshop that was created for and provided to educators who were interested in implementing more playful pedagogies in their educational settings. The workshop focused primarily on meeting the needs of all learners through meaningful and engaging practices which focused on playful learning within teaching, incorporating Universal Design principles and the integration of Nature-Based Learning (NBL). Two separate sessions were provided with approximately 20-25 participants in each session. Each workshop was one hour in length and included participants with a variety of teaching roles, including pre-kindergarten teachers, K-2 teachers and coaches, English as a New Language (ENL) teachers, special education (elementary and secondary) teachers, art educators, physical education teachers, speech and language pathologists, in addition to others. The authors recommend that due to the dearth of the intersection of play, UDL, and NBL, educators should continue to purposefully integrate these strategies into professional development opportunities and classroom pedagogy, while also providing additional professional development emphasizing inclusive methods.
Keywords: play; universal design for learning; nature-based learning; professional development; teacher education